Asymptomatic myocardial dysfunction was revealed by feature tracking cardiac magnetic resonance imaging in patients with primary Sjögren's syndrome. (25th October 2021) - Yokoe, Isamu; Kobayashi, Hitomi; Nishiwaki, Atsuma; Nagasawa, Yosuke; Kitamura, Noboru; Haraoka, Masaki; Kobayashi, Yasuyuki; Takei, Masami; Nakamura, Hideki
Abstract: Aim: To evaluate subclinical left ventricular (LV) regional dysfunction in patients with primary Sjögren's syndrome (pSS) using feature tracking cardiac magnetic resonance (FT‐CMR) imaging and to identify pSS characteristics independently associated with LV regional dysfunction. Method: Fifty patients with pSS and 20 controls without cardiovascular disease underwent non‐contrast CMR imaging. Labial gland biopsy was performed in 42 patients (84%). Disease activity was assessed using the European League Against Rheumatism Sjögren's syndrome disease activity index (ESSDAI). LV global longitudinal strain (GLS), global circumferential strain (GCS), and global radial strain (GRS) were measured using FT‐CMR. Results: No significant differences in cardiovascular risk factors were found between the pSS group and controls. The pSS group had significantly lower GLS ( P = .015) and GCS ( P = .008) than the control group. Multiple linear regression analysis indicated that GCS was significantly associated with Raynaud's phenomenon ( P = .015), focus score ≥2 ( P = .032), and total ESSDAI score ≥8 ( P = .029). Conclusion: FT‐CMR can reveal subclinical LV regional dysfunction in patients with pSS without cardiovascular disease. Furthermore, patients with pSS and Raynaud's phenomenon, a focus score ≥2, or an ESSDAI score ≥8 were considered to be at high risk for myocardial dysfunction.